Perception of Anxiety Levels in Families of Patients Given Informed Consent Ventilator Installation at ICU Cileungsi Hospital - Reni Anggraeni Aprillia; Abdul Khamid; Achmad Fauzi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Through a ventilator, patients who have difficulty breathing independently can be helped to breathe and get air like breathing normally. The ventilator machine will regulate the process of inhaling and exhaling in the patient. The ventilator will pump air for a few seconds to deliver oxygen to the patient's lungs, then stop pumping to get the air out on its own from the lungs. Based on data obtained in the ICU room of Cileungsi Hospital in the period 2021 from January 2021 to October 2021 from 359 patients treated. Knowing the perception of anxiety levels in the families of patients who will be given Informed Consent ventilator installation in ICU Cileungsi Hospital. Design: The study used a total sampling of 21 respondents. Data collection is done with questionnaires. Methdos: The type of research that will be used is this Quantitative research method using quasi eksperimente method using the design of Nonevaquivalent Control Group Desaign with a sample of the patient's family who will be given Informed Consent ventilator installation in the ICU Room of Cileungsi Hospital. Results: The most anxiety levels of respondents were the category of mild anxiety amounting to 9 respondents (42.9%), the least anxiety levels obtained by the weight category amounted to 2 respondents (9.5%), while the respondents of the non-anxious category amounted to 7 respondents (33.3%), and moderate category respondents amounted to 3 respondents (14.3%). With the results of the statistical test obtained P Value .000 < 0.05. Which means that there is an effect of the installation of ventilators of respondents on the level of anxiety. Conclusions: Based on the results of research conducted on, perception of anxiety levels in the families of patients who are informed consent ventilator installation in the ICU room of Cileungsi Hospital, it can be concluded: of the 21 respondents based on the level of anxiety of the most respondents is the category of mild anxiety amounted to 9 respondents (42.9%), the level of anxiety at least obtained by the weight category amounted to 2 respondents (9.5%), While the respondents of the category are not anxious amounted to 7 respondents (33.3%), and moderate category respondents amounted to 3 respondents (14.3%).